Evaluasi User Experience Aplikasi Mobile Pemesanan Makanan Online dengan Metode Design Thinking (Studi Kasus GrabFood) - Muhammad Azmi; Agi Putra Kharisma; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The development of internet and mobile applications has brought us a step further in applying technology in modern life. One of them is an application to get goods and services in the form of an online food ordering application. Various online food ordering applications emerge by presenting a unique user experience and user interface, one of them is GrabFood. This study will examine the user experience of the GrabFood application and conduct evaluations to assess and also looking for the shortcomings that exist in the user experience of the GrabFood application. The method in this research uses design thinking as a method in designing and developing user experiences. Data collection in this study using interview methods and by conducting usability testing of five respondents. The usability aspects tested in this study are aspects of effectiveness, efficiency, and user satisfaction. Based on the results of the research, there is an increase in efficiency aspects ranging from 33,1 to 67,4 percent and user satisfaction aspects ranging from 3,3 to 25,9 percent in the evaluation results (GrabFood prototype).